ナンキョク ニオケル カンキョウ ホウシャセン ノ カンソク ケイカク g. ショウライ ケイカク ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 2 - 小玉, 正弘; コダマ, マサヒロ; KODAMA, Masahiro (1980)
P(論文) 南極地域における環境放射線測定の目的と意義について考察し,昭和基地ならびにその周辺環境-大気中,地中,雪水中-での自然放射線測定の具体案についで述べる.とくに,この種の放射線・放射能観測が,資源探査への科学技術的応用のみでなく,これまでの各関連学問分野の積極的協力により,新しい境界分野の発展につながることを強調する. Taking into account the physical aim and significance of measurements of environmental radiations including artificial origins in Antarctica, some plans are proposed for measurements at Syowa Station and its surrounding regions. In particular, it is stressed that the environmental radiation measurements would bear a close relation not only with a technological application to exploration of energy resources but also with development of a new field of study over the existing disciplines such as meteorology, glaciology, earth and space sciences, etc. departmental bulletin paper